The Rebbe, the Messiah, and the Scandal of Orthodox Indifference : With a New Introduction. - Berger, David (Littman library of Jewish civilization (Series), 2008)
This book argues that the new belief that the late Lubavitcher Rebbe is the Messiah endangers Judaism and urges that its adherents be excluded from Orthodoxy.